FolC2‐mediated folate metabolism contributes to suppression of inflammation by probiotic Lactobacillus reuteri. Issue 5 (28th June 2016) - Thomas, Carissa M.; Saulnier, Delphine M. A.; Spinler, Jennifer K.; Hemarajata, Peera; Gao, Chunxu; Jones, Sara E.; Grimm, Ashley; Balderas, Miriam A.; Burstein, Matthew D.; Morra, Christina; Roeth, Daniel; Kalkum, Markus; et al.
Abstract: Bacterial‐derived compounds from the intestinal microbiome modulate host mucosal immunity. Identification and mechanistic studies of these compounds provide insights into host–microbial mutualism. Specific Lactobacillus reuteri strains suppress production of the proinflammatory cytokine, tumor necrosis factor (TNF), and are protective in a mouse model of colitis. Human‐derived L. reuteri strain ATCC PTA 6475 suppresses intestinal inflammation and produces 5, 10‐methenyltetrahydrofolic acid polyglutamates. Insertional mutagenesis identified the bifunctional dihydrofolate synthase/folylpolyglutamate synthase type 2 ( folC2 ) gene as essential for 5, 10‐methenyltetrahydrofolic acid polyglutamate biosynthesis, as well as for suppression of TNF production by activated human monocytes, and for the anti‐inflammatory effect of L. reuteri 6475 in a trinitrobenzene sulfonic acid‐induced mouse model of acute colitis. In contrast, folC encodes the enzyme responsible for folate polyglutamylation but does not impact TNF suppression by L. reuteri . Comparative transcriptomics between wild‐type and mutant L. reuteri strains revealed additional genes involved in immunomodulation, including previously identified hdc genes involved in histidine to histamine conversion. The folC2 mutant yielded diminished hdc gene cluster expression and diminished histamine production, suggesting a link between folate and histadine/histamine metabolism. The identification of genes and gene networks regulating production of bacterial‐derived immunoregulatory molecules may lead to improved anti‐inflammatory strategies for digestive diseases. Abstract : The bifunctional dihydrofolate synthase/folylpolyglutamate synthase type 2 ( folC2 ) gene is necessary for 5, 10‐methenyltetrahydrofolic acid production by Lactobacillus reuteri, while the folC gene encodes the enzyme responsible for polyglutamylation of 5, 10‐methenyltetrahydrofolate. The folC2 gene is important for suppression of the proinflammatory cytokine, tumor necrosis factor (TNF), in vitro, and for protection against trinitrobenzene sulfonic acid (TNBS)‐induced colitis and mucosal inflammation in vivo. In addition, there is a link between 5, 10‐methenyltetrahydrofolic acid production and histamine, a known potent immunoregulatory molecule produced by probiotics. Specifically, the folC2 mutant yields diminished expression of the hdc gene cluster, which is responsible for the conversion ofl ‐histidine to histamine as well as diminished histamine production.